2000
DOI: 10.1111/j.1151-2916.2000.tb01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Current–Voltage Characteristics of Multicomponent Vanadium‐Doped Zinc Oxide Varistors

Abstract: The effects of the oxide additives MnO 2 , Co 3 O 4 , and Sb 2 O 3, commonly incorporated in commercial Bi 2 O 3 -doped ZnO varistors, on the current-voltage characteristics and microstructure of 0.25 mol% V 2 O 5 -doped ZnO varistors have been studied. MnO 2 is the most significant additive in terms of its effects on varistor performance. Varistor performance can also be improved by increasing the V 2 O 5 content to 0.5 mol% in a ZnO ceramic containing 1 mol% MnO 2 . Further increases in the V 2 O 5 content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 34 publications
(40 reference statements)
5
60
0
1
Order By: Relevance
“…Previously, it has not been possible to make functional varistor using this kind of ZnO varistor materials sintered at low temperature (900°C). Much research has been done with ZnO-V 2 O 5 ceramics, but the reported [15][16][17][18][19]. Functional varistor compositions sinterable at 900°C using the polymerized complex methods have also been researched.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has not been possible to make functional varistor using this kind of ZnO varistor materials sintered at low temperature (900°C). Much research has been done with ZnO-V 2 O 5 ceramics, but the reported [15][16][17][18][19]. Functional varistor compositions sinterable at 900°C using the polymerized complex methods have also been researched.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12]15]. However, the low-temperature sintered composition here researched with 10 wt.% of glass PZB showed V bk value low enough for low voltage applications [6].…”
Section: Discussionmentioning
confidence: 99%
“…Entre tales óxidos se encuentran el de praseodimio y otras tierras raras, el de bario, e incluso los de cationes pequeños como el vanadio (32)(33)(34)(35)(36), aunque éste último no entra en la red del ZnO no por su tamaño sino porque forma fases secundarias activas en la interfase de los granos de ZnO. Pero sin duda el que mejor contribuye a la formación del comportamiento varistor ("varistor forming dopant") es mitad de las tetraédricas desocupadas, que va a facilitar tanto la incorporación de dopantes externos a la red como la difusión de sus propios defectos intrínsecos.…”
Section: Papel De Los Dopantes: Sistema Base Zno-bi 2 O 3 -Sb 2 Ounclassified
“…In addition to larger exciton binding energy, the ability to grow the single crystal substrates makes the material more promising. The new perspectives of ZnO include blue/UV optoelectronics, transparent electronics, spintronics, and sensors [2,3]. In recent years, rare earth (RE) doped oxide semiconductors (e.g., ZnO, SnO 2 ) have been the focus of numerous investigations because of their short luminescence life time, cathodoluminescence, electro-luminescence, and possibility to tune the emission properties with crystallite size [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%